The Meaning of Denotation, Connotation, and Myth Used in Ariana Grandeâ€™s "God is A Woman" Song Lyrics - Ahmad Jafar; La Aso; Neil Amstrong (ELITE: Journal of English Language and Literature, 2021)
This study focused on God is a woman song Lyrics. The writer took song lyrics as primary data and used a qualitative descriptive method that explained descriptively how the meaning used in Ariana Grandeâ€™s God is a woman song lyrics. The theory used in the study is semiotics, in particular, is the theory used by Roland Barthes. The result of this study based on Roland Barthes Semioticâ€™s theory in a way of denotative it is about sex and how she claims the chemistry will be so incredible that the guy is going to think she is God and in a way of connotative Ariana Grande campaigned for a struggle for gender equality and she showed off women's energy and independence. While the myth is God is a woman which this sentence represents gender differences in life. The answer to dismantling patriarchy is not raising a matriarchy in its place. But building our understanding of, as Ariana Grande puts it, "God as a woman," will help counterbalance almost every human's internalized beliefs that our creator is a man, a father, a guy in the sky. God is our mother, our father, our parents. Come to think of it, if God can be referred to with the masculine pronoun â€œheâ€, why is not okay for us to also use the female pronoun â€œsheâ€ when referring to God.